1993
DOI: 10.1002/bip.360330604
|View full text |Cite
|
Sign up to set email alerts
|

Differential binding of the enantiomers of chloroquine and quinacrine to polynucleotides: Implications for stereoselective metabolism

Abstract: Interaction of the antimalarial drugs quinacrine and chloroquine with DNA has been studied extensively in order to understand the origin of their biological activity. These studies have shown that they bind to DNA through an intercalative mode and show little sequence specificity. All previous experiments were carried out using the racemic form of these drugs. We have investigated the binding of the enantiomeric forms of quinacrine and chloroquine to synthetic polynucleotides poly(dA-dT).poly(dA-dT) and poly(d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The effects of both CQDP and 6 on the secondary structure of CT DNA have been reported [57,76] and they agree with our results. CQDP is a chiral molecule and the (+) and (−) enantiomers give mirror image CD spectra [57], which explains the lack of CD bands for the racemate used in our experiments.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The effects of both CQDP and 6 on the secondary structure of CT DNA have been reported [57,76] and they agree with our results. CQDP is a chiral molecule and the (+) and (−) enantiomers give mirror image CD spectra [57], which explains the lack of CD bands for the racemate used in our experiments.…”
Section: Resultssupporting
confidence: 93%
“…CQDP is a chiral molecule and the (+) and (−) enantiomers give mirror image CD spectra [57], which explains the lack of CD bands for the racemate used in our experiments. Additionally, it has been determined by both spectrophotometric titrations and CD spectroscopy of pure CQDP enantiomers that the (−) enantiomer has a higher binding affinity for a given polynucleotide than the (+) one, with a ratio of 1.29 and 1.28 for poly (dG-dC).poly (dG-dC) and poly (dA-dT).poly (dA-dT) respectively [57]. This preferential binding of (−)-CQDP causes a change in the enantiomeric composition of the remaining drug not-bound to DNA, thus generating optical activity due to excess of free (+) CQDP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinacrine has two optical isomers (enantiomers) with a chiral center in the middle section of its ‘tail’ [104]. This results in two different positions of the tail in the minor groove: the S -enantiomer tail is directed against the direction of the minor groove, while the R -enantiomer tail is positioned along the minor groove (Figure 2A).…”
Section: How Quinacrine Interacts With Dnamentioning
confidence: 99%
“…46 We recently demonstrated that the binding of anti-dsDNA antibodies as measured by the modified Farr assay is reduced by the addition of hydroxychloroquine in vitro. 47 This effect is likely to be due to the high protein-binding capacity of hydroxychloroquine, 48 and intercalation of DNA (if sharing this property with chloroquine), 49,50 potentially modifying critical autoepitopes. Whether this affects the pathogenesis of human lupus nephritis is unknown.…”
Section: Reducing the Binding Of Autoantibodiesmentioning
confidence: 99%